2019
DOI: 10.5194/esurf-2019-48
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lithology and orographic precipitation control river incision in the tropical Andes

Abstract: Process-based geomorphic transport laws enable to assess the impact of rainfall variability on bedrock river incision over geological timescales. However, isolating the role of rainfall variability on erosion remains difficult in natural environments in part because the variability of rock strength and its resistance to incision are poorly constrained. Here, we explore spatial differences in the rate of bedrock river incision in the tropical Andes. The Ecuadorian Andes are characterized by strong rainfall grad… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 82 publications
(129 reference statements)
0
16
0
Order By: Relevance
“…Amongst these intrinsic forcings, the effect of differential lithology on fluvial morphology has been a recent focus of geomorphological studies (e.g. Bernard et al, 2019;Campforts et al, 2019;Forte et al, 2016;Kirby et al, 2003;Peifer Bezerra, 2018;Seagren & Schoenbohm, 2019;Strong et al, 2019;Thaler & Covington, 2016;Yanites et al, 2017). Rivers flowing over harder rocks tend to have steeper channels and affect the overall landscape morphology (e.g.…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Amongst these intrinsic forcings, the effect of differential lithology on fluvial morphology has been a recent focus of geomorphological studies (e.g. Bernard et al, 2019;Campforts et al, 2019;Forte et al, 2016;Kirby et al, 2003;Peifer Bezerra, 2018;Seagren & Schoenbohm, 2019;Strong et al, 2019;Thaler & Covington, 2016;Yanites et al, 2017). Rivers flowing over harder rocks tend to have steeper channels and affect the overall landscape morphology (e.g.…”
Section: Accepted Articlementioning
confidence: 99%
“…Careful acknowledgement of lithological heterogeneities still permits the interpretation of climatic and tectonic signals from river morphology (e.g. Campforts et al, 2019;Kirby et al, 2003), but can also confuse the signal (e.g. Strong et al, 2019) and potentially lead to misinterpretation.…”
Section: Accepted Articlementioning
confidence: 99%
“…While ME is commonly used to evaluate models in geomorphic research (e.g. de Vente et al, 2013;Campforts et al, 2019), it is also highly sensitive to outliers. As complementary measures, we therefore also calculated the overall Bias (see Eq.…”
Section: Assessing the Model Performancementioning
confidence: 99%
“…A main finding of those authors is that the role of allogenic fluvial response (i.e. transient adjustment to an external perturbation) can only be understood when considering autogenic fluvial dynamics such as the existence of incision thresholds (Snyder et al, 2003;Lague et al, 2005) and the internal lithological heterogeneity in a landscape (Campforts et al, 2019;Glade et al, 2019). However, the role of landslides in long-term landscape evolution, and especially the dynamic interaction between river incision and landslide activity, is only poorly understood.…”
Section: )mentioning
confidence: 99%
“…CRN data has been used to calibrate river incision models that explicitly integrate the stochastic nature of fluvial incision over time (DiBiase and Whipple, 2011;Scherler et al, 2017;Campforts et al, 2019). However, CRN data is sensitive to landslide activity (Niemi et al, 2005;Yanites et al, 2009;Wang et al, 2017) and the calibration of stochastic river incision models has been shown to be sensitive to landslide activity (Campforts et al, 2019). HyLands directly simulates stochastic landsliding and hence enables explicit simulation of the impact of landsliding on CRN-derived erosion rates, making them a promising tool to constrain HyLands.…”
Section: Calibration Of Hylandsmentioning
confidence: 99%